Buddhist Amulets: Religious Artifacts and Their Latent Political Significance: Buddhist Amulets: Religious Artifacts and Their Latent Political Significance - Soathongtong, Norapat; Chaiyanich, Parinu; Rungrot, Lakkana; Tonghan, Pattanapong; Jantarat, Warin (RATANABUTH JOURNAL, 2026)
The fact that collectors of amulets and religious artifacts today lack understanding of the political meanings conveyed by them leads to different interpretations of the purpose of amulets and religious artifacts in different areas. This research therefore aims to (1) study the history of amulets in Thailand and (2) study the political implications through Buddhist artifacts. It is qualitative research using document study, interviews using a semi-structured questionnaire from 18 key informants, and participatory observation. The findings revealed that: 1) To study the historical development of amulets in Thai society. These amulets were found to be made from materials and technologies consistent with the region where they were created, allowing for the study and understanding of the production process and extending to the political and environmental context of that era. 2) Analyzing the political implications reflected in Buddhist artifacts were found to be related to the imbalance in the power structure of the state, which consists of political, economic, and legal structures. This opened the door to the accumulation of local power or regionalism, leading to compensation for this imbalance through various methods. Religious artifacts are therefore one of the reflections of this imbalance and show the image of political control and social organization using religious artifacts as a medium. From the study, three issues can be presented: the political history aspect, the regionalism aspect, and the religious philosophy aspect. In summary, the study of the political implications of religious artifacts encompasses aspects of political history, regionalism, and religious philosophy. The overlap of these three dimensions gives rise to universal amulets, such as the Benjapakee (five most revered amulets) which serve as the central standard for amulet collecting, and regional amulets with distinct details that vary from region to region